AN ANALYSIS OF PROPPIAN’S ARCHETYPES ON CHARACTERS IN ZOOTOPIA MOVIE - Liga Sandi Siregar; Aulia Putri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
Watching movie has become as one of activity choices by people in spare time. This phenomenon can be influenced by the way its presented. As one of literary works, movie has fiction elements, intrinsic elements and extrinsic elements.Intrinsic element is the elements that build the literary work itself. The elements consist of plot, theme, background, character, and point of view. Character has an important role in building a fictional story.A character can be divided into some categories, they are protagonist character, antagonist character, typical character, supporting character,neutral character, etc. a characters can be created by use the seven sphere of acttion which are the Hero, the the Villain, the Donor, the Helper, the Princess, the Dispatcher and the False Hero.Therefore, this research aims focused on analyzing the seven archetypes in Vladimir Propp’s Morphology of the Folktale theory appear in Zootopiamovie. Finally, the findings show that there are 6 out of 7 archetypes that appeared in this movie. The Helper was the most dominant Archetypes that showed in the film with 4 data, followed by Hero, Villain, Princess, and Dispatcher with 2 data and the least dominance Archetypes that showed in the movie was Donor with 1 data.